The combined use of three widely available biochemical markers as predictor of organ failure in critically ill patients. (17th August 2016) - Helliksson, Fredrik; Wernerman, Jan; Wiklund, Lars; Rosell, Jon; Karlsson, Mathias
Abstract: Background: We hypothesized that lactate dehydrogenase, LDH/albumin ratio in combination with or without magnesium (Mg 2+ ) could predict organ failure in critically ill adult patients. The aim of this study was to describe a new risk index for organ failure or mortality in critically ill patients based on a combination of these routinely available biochemical plasma biomarkers. Methods: Patients ≥ 18 years admitted to the intensive care unit (ICU) were screened. Albumin and LDH were analyzed at the time of admission to ICU ( n = 347). Organ failure assessed with 'Sequential Organ Failure Assessment' (SOFA) score was used, and 30-day mortality was recorded. The predictive value of the test was calculated using the areas under the receiving operating characteristic (ROC) curve. Results: The LDH/albumin ratio was higher in patients who developed organ failure as compared to those who did not ( p < 0.001). The areas under the ROC curve were 0.77 both for prediction of multiple organ failure and for 30-day mortality. In a subgroup of patients ( n = 183) admitted to ICU from the emergency department, the predictive values were 0.86 and 0.80, respectively. Conclusion: The LDH/albumin ratio at ICU admission was associated with the development of multiple organ failure and 30-day mortality in this prospective study. The clinical value of this biomarker as a predictor of organ failure in critically ill patients is yet to be defined.